Tractor frame - ZHOU YOUMING; CHEN SHAOMIN; LI DEGUANG; LAN JUN; LI JUN; LIU TAOFENG; LU KAIYANG (2021)
The invention relates to the technical field of commercial vehicles, and discloses a tractor frame which comprises a left longitudinal beam, a right longitudinal beam, a front sealing plate, a transmission cross beam, a rear suspension front support cross beam and a rear cross beam. The front sealing plate is connected to the front end of the left longitudinal beam and the right longitudinal beam. The transmission cross beam and the rear suspension front support cross beam are both connected to the middle of the left longitudinal beam and the middle of the right longitudinal beam, traction base connecting plates are arranged on the left longitudinal beam and the right longitudinal beam; and first grooves are formed in the bottoms, located on the traction base connecting plates, of the left longitudinal beam and the right longitudinal beam. The rear end of the left longitudinal beam and the rear end of the right longitudinal beam are both provided with notches, and the rear cross beam is connected between the